2019
DOI: 10.1038/s41593-019-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system regeneration is driven by microglia necroptosis and repopulation

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
202
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(222 citation statements)
references
References 20 publications
(21 reference statements)
14
202
1
5
Order By: Relevance
“…In both treated and untreated patients, we found that many macrophages expressed an intermediate activation status. Since efficient remyelination necessitates repopulation of pro‐inflammatory microglia by pro‐regenerative microglia, this finding supports that the activation status of microglia/macrophages is dynamic in vivo and occurs as a continuum, with the classically activated pro‐inflammatory and alternatively activated anti‐inflammatory phenotypes on either end of this spectrum . We finally found that the presence of these intermediately activated cells overexpressing markers of alternative activation was associated with evidence of remyelination in HSCT‐treated patients’ white matter.…”
Section: Discussionsupporting
confidence: 76%
“…In both treated and untreated patients, we found that many macrophages expressed an intermediate activation status. Since efficient remyelination necessitates repopulation of pro‐inflammatory microglia by pro‐regenerative microglia, this finding supports that the activation status of microglia/macrophages is dynamic in vivo and occurs as a continuum, with the classically activated pro‐inflammatory and alternatively activated anti‐inflammatory phenotypes on either end of this spectrum . We finally found that the presence of these intermediately activated cells overexpressing markers of alternative activation was associated with evidence of remyelination in HSCT‐treated patients’ white matter.…”
Section: Discussionsupporting
confidence: 76%
“…The data indicate that TREM2 deficiency had no impact on the initial demyelination, but affected subsequent remyelination when the cuprizone treatment was prolonged, most likely by impairing myelin removal as well as myelin regeneration, which further supports a protective role for CD11c+ microglia in this paradigm (144,147). Additionally, it was reported that microglial necroptosis in circumstances of lysophosphatidylcholine demyelination leads to repopulation by pro-regenerative CD11c+ microglia, as blocking of this mechanism prevented remyelination (148). Of note, demyelination induced by mouse hepatitis virus also led to enrichment of CD11c+ microglial gene signature in the spinal cord (149).…”
Section: Multiple Sclerosismentioning
confidence: 74%
“…Of note, induction of this phenotype was not observed upon microglia exposure to Escherichia coli, zymosan particles (75), or microparticles (Marczynska et al, unpublished), suggesting that induction of CD11c+ microglia is a tightly controlled reaction to local cell damage or apoptosis, rather than to phagocytosis itself. Interestingly, microglial necroptosis in demyelination models leads to brain repopulation with CD11c+ microglia from nestin+ resident microglia (148). Similarly, nestin+ microglia colonizing the brain after microglia ablation expressed surface CD11c (98).…”
Section: Cell Deathmentioning
confidence: 99%
“…Detailed analysis of the Csf1r mutant phenotypes could therefore contribute to the identification of specific and universal features of organism-wide macrophage development. In addition, it is important to understand the systemic effects of CSF1R inhibition on macrophages, as inhibition of CSF1R is a clinical strategy for the intentional depletion of macrophages in various disease contexts, including Alzheimer’s disease, brain injury and cancer (Edwards et al, 2019; Lloyd et al, 2019; Tap et al, 2015; Webb et al, 2018).…”
Section: Introductionmentioning
confidence: 99%